Digital Spatial Infrastructures and Worldviews in Pre-Modern Societies. - Petrulevich, Alexandra; Skovgaard Boeck, Simon (Amsterdam : Arc Humanities Press, 2023)
This volume examines new ways to design, develop, explore, and visualize spatial datasets to investigate spatial dimensions and world perceptions in pre-modern sources and societies.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books